Application of Fractional Calculus in Control and Electromagnetism - Tenreiro Machado, J. A. (2007)
This article illustrates two applications of fractional calculus (FC) in engineering. It has been recognized the advantageous use of this mathematical tool in the modeling and control of many dynamical systems. In this perspective, this paper investigates the use of FC in PID tuning and electrical potential.